2013
DOI: 10.1001/jamaoto.2013.1060
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Repeated Adenoidectomy in Children

Abstract: Age younger than 5 years and adenoidectomy without tonsillectomy were identified as important risk factors for repeated adenoidectomy in children. Parents should be made aware of the increased risk of adenoid regrowth if surgery is performed at a young age. Children undergoing adenoidectomy alone should be followed up carefully to monitor for symptom recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 14 publications
(26 reference statements)
1
27
0
Order By: Relevance
“…36 Repeat adenoidectomy is sometimes required for persistent or recurrent symptoms, with the likelihood of repeat adenoidectomy being 2.5 times higher in children under 5 years of age at the time of the first surgery and also higher in those whose first surgery was adenoidectomy alone. 37 Adenoidectomy was the treatment option for 17% (4/23; 3 with PS and 1 MS OSA) of the children who were treated in our study; however, SDB remained unresolved in only one of those children (one with PS). As many children in our cohort had PS or Mild OSA, we chose to include nasal steroids in the treatment group as this is a recognized treatment for mild OSA, 38 rather than omitting these children.…”
Section: Discussionmentioning
confidence: 66%
“…36 Repeat adenoidectomy is sometimes required for persistent or recurrent symptoms, with the likelihood of repeat adenoidectomy being 2.5 times higher in children under 5 years of age at the time of the first surgery and also higher in those whose first surgery was adenoidectomy alone. 37 Adenoidectomy was the treatment option for 17% (4/23; 3 with PS and 1 MS OSA) of the children who were treated in our study; however, SDB remained unresolved in only one of those children (one with PS). As many children in our cohort had PS or Mild OSA, we chose to include nasal steroids in the treatment group as this is a recognized treatment for mild OSA, 38 rather than omitting these children.…”
Section: Discussionmentioning
confidence: 66%
“…One of the main purposes of this study was to clarify the revision rate of pediatric adenoidectomy, and our results re-total, 44 potentially pertinent studies were identified. Finally, 16 studies were included in the quantitative analyses ( Table 2) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) . Table 2 shows the basic characteristics of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regrowth of adenoid tissue is also a potential concern following adenoidectomy. In a large study of over 10,000 adenoidectomies, it was found that the rate of revision adenoidectomy was 1.5%, and children under 5 years of age were 2.5 times more likely to have a second adenoidectomy [41]. Another study reported a revision adenoidectomy rate of 9%, with a median re-operation time of 16 months following initial procedure [5].…”
Section: Adenoid Regrowth and Revision Adenoidectomymentioning
confidence: 99%